2014
DOI: 10.1155/2014/462084
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepaticain Some Buffaloes and Cattle by PCR and Microscopy

Abstract: Fasciolosis is the burning problem of the livestock rearing community having huge morbidity, mortality, and economic losses to livestock industries in our country Pakistan. The faecal and liver biopsy samplings were examined by polymerase chain reaction (PCR) and microscopy technique during the entire study. A total of 307 samples including 149 samples from Karak and 158 samples from Kohat abattoirs were examined by PCR method and overall prevalence of fasciolosis was 5.86% (18/307), amongst theses 8.05% (12/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Fascioliasis is an extremely serious disease that causes enormous losses in cattle production and in the related meat, milk, and leather industry as Fascciola spp. could be found in ectopic location as the skin [15]. Although the prevalence of fascioliasis recorded in the present study was low (16.81%), which may not be a regular consideration of its prevalence in New Valley, Egypt, analysis of the different immunological and biochemical parameters emphasizes on how the infestation of F. hepatica even at such a low prevalence rate affects the quality of meat and meat products, particularly when apparently clinically normal animals are allowed to be slaughtered after antemortem examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fascioliasis is an extremely serious disease that causes enormous losses in cattle production and in the related meat, milk, and leather industry as Fascciola spp. could be found in ectopic location as the skin [15]. Although the prevalence of fascioliasis recorded in the present study was low (16.81%), which may not be a regular consideration of its prevalence in New Valley, Egypt, analysis of the different immunological and biochemical parameters emphasizes on how the infestation of F. hepatica even at such a low prevalence rate affects the quality of meat and meat products, particularly when apparently clinically normal animals are allowed to be slaughtered after antemortem examination.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only F. hepatica was detected at the study site (100%), as revealed by postmortem examination, whereas F. gigantica and mixed specifies were not detected, which is consistent with that reported by Tulu [24], who stated that F. hepatica (100%) was the predominant species of zoonotic liver flukes found at an abattoir in Ambo district, Ethiopia. The prevalence rate of F. hepatica can reach up to 77% in developing countries [15].…”
Section: Discussionmentioning
confidence: 99%
“…Robles‐Pérez, Martínez‐Pérez, Rojo‐Vázquez, and Martínez‐Valladares () also detected the infection at 2 wpi but by a conventional PCR, which is a less time consuming method, and amplifying a 292 bp fragment of the ITS2 gene. Ayaz, Ullah, AbdEl‐Salam, Shams, and Niaz () compared the prevalence of F. hepatica in cattle and buffaloes using the FEC and a PCR method; authors showed the higher sensitivity of the molecular technique. Additionally, to differentiate between species, F. hepatica and F. gigantica , a single‐step multiplex PCR was developed for simultaneous detection using faecal samples (Le et al., ); both species overlap in distribution in some countries of Africa and Asia and have similar egg morphology, making identification from faecal samples difficult.…”
Section: Diagnosismentioning
confidence: 99%
“…Ayaz et al. (2014) compared the PCR and microscopy for the diagnosis of F. hepatica in some buffaloes and cattle. Their results showed that PCR was a more sensitive method of Fasciola diagnosis than microscopy.…”
Section: Discussionmentioning
confidence: 99%